Epigallocatechin-3-Gallate Suppresses BMP-6-Mediated SMAD1/5/8 Transactivation of Hepcidin Gene by Inducing SMILE in Hepatocytes - Yu-Ji Kim; Woo-Ram Park; Byungyoon Choi; Hueng-Sik Choi; Don-Kyu Kim (MDPI AG, 2021)
Hepcidin, a major regulator of systemic iron homeostasis, is mainly induced in hepatocytes by activating bone morphogenetic protein 6 (BMP-6) signaling in response to changes in the iron status. Small heterodimer partner-interacting leucine zipper protein (SMILE), a polyphenol-inducible transcriptional co-repressor, regulates hepatic gluconeogenesis and lipogenesis. Here, we examine the epigallocatechin-3-gallate (EGCG) effect on BMP-6-mediated SMAD1/5/8 transactivation of the hepcidin gene. EGCG treatment significantly decreased BMP-6-induced hepcidin gene expression and secretion in hepatocytes, which, in turn, abated ferroportin degradation. SMILE overexpression significantly decreased BMP receptor-induced hepcidin promoter activity. SMILE overexpression also significantly suppressed BMP-6-mediated induction of hepcidin mRNA and its secretion in HepG2 and AML12 cells. EGCG treatment inhibited BMP-6-mediated hepcidin gene expression and secretion, which were significantly reversed by SMILE knockdown in hepatocytes. Interestingly, SMILE physically interacted with SMAD1 in the nucleus and significantly blocked DNA binding of the SMAD complex to the BMP-response element on the hepcidin gene promoter. Taken together, these findings suggest that SMILE is a novel transcriptional repressor of BMP-6-mediated hepcidin gene expression, thus contributing to the control of iron homeostasis.